The use of songs to enhance listening skill in children of kindergarten (5-7) - Ávila, Cecilia; Bautista, Mayra
Since listening is one of the most important skills when learning a language, it is important to encourage learners from a very early age. English teachers must find effective activities in order to develop this skill. Songs are therefore suitable for teaching English as a foreign language to children of kindergarten, who are the main target of our project. English teachers must know that children learn by playing, jumping, touching, etc. We should therefore consider the abilities of our young students and take advantage of them, because children play the main role in this process. Teachers are facilitators in the teaching ? learning process. For this reason, we have selected and created songs and activities in order to motivate our children to learn English. These activities constitute an example of how teachers can conduct their EFL classes. English teachers will find the proposed activities useful and motivating. These activities can easily be applied in the EFL classroom in order to enhance children?s listening skill as well as their participation in the learning process.